Development of welded stiffener plates using dissimilar and similar metal joining technique - Ishak, M.; Idris, Siti Rabiatull Aisha; Ahmad Shah, Luqman Hakim; Rejab, Mohd Ruzaimi Mat (2017)
The advantage of reinforcing a plate by stiffeners lies in a rise of strength and stability with minimum increase of weight to the overall structures. Consequently, rational design and parametric studies of the response of stiffened plates have long been a major concern of researchers. Over the past years, a vast number of papers have been published at the theoretical and experimental level, reporting studies of the influence of various loading and boundary conditions, different locations and sizes of stiffeners, assembling techniques and fabrication methods, and materials used in manufacturing. This work was carried out on dissimilar metal joining of the hard-to-weld aluminum alloys, which has become an important application in the modern industries. The study aims on producing defects-free welds of high strength AA7075-T6 and AA2024-T351 aluminum alloys by the friction stir welding (FSW), which has been proposed as an alternative welding method. The experimental setup was developed through introducing proper design of welding tool and backing/clamping system, considering the process variables (welding speeds, tool tilt angle, clamping force, dwell sequence and relative materials position and orientation). Different pin tool profiles (cylindrical and tapered, smooth and threaded, flatted and non-flatted) were investigated in conjunction with varying levels of machine variables through the central composite design method. The purpose of this work is to outline the research studies that have been conducted on stiffened plates in general. Developed theoretical and numerical methods, finite element analyses and experimental investigations have been explored in this survey with a brief summary of some results obtained by the researchers. The dissimilar AA7075-AA2024 weld strength of about 400 MPa, which represents an efficiency of 89% was recorded when the softer AA2024 alloy was fixed on the advancing side at 900 rpm of spindle speed, 100 mm/min of traverse rate, 3° of tilting angle and moderate clamping pressure of 3 kN. The results clarified that the effect of backing and clamping materials on the weld strength is changed related to the applied welding speed. Moreover, a considerable difference in process temperature was noticed between the advancing and retreating sides of the weld. The outcomes of the present study provided advanced knowledge for the future work in dissimilar metal joining.